Activation of PIEZO1 Attenuates Kidney Cystogenesis In Vitro and Ex Vivo - Qingfeng Fan; Mohamad Hadla; Zack Peterson; Grace Nelson; Hong Ye; Xiaofang Wang; Jean Marc Mardirossian; Peter C. Harris; Seth L. Alper; Y.S. Prakash; Arthur Beyder; Vicente E. Torres; et al. (Kidney360)
Key Points. PIEZO1 activation reduces cystogenesis: Yoda1 activates PIEZO1, raising calcium and lowering cAMP, reducing cyst growth in autosomal dominant polycystic kidney disease models. Context-dependent role of PIEZO1: PIEZO1 knockout in mice with or without polycystic kidneys does not affect cyst formation, suggesting redundancy in mechanosensitive pathways. Therapeutic potential: Findings support PIEZO1 activation as a part of combination therapy to slow cyst growth in autosomal dominant polycystic kidney disease, needing more in vivo studies. Background. The disruption of calcium signaling associated with polycystin deficiency is a key factor in abnormal epithelial growth in autosomal dominant polycystic kidney disease. Calcium homeostasis can be influenced by mechanotransduction. The mechanosensitive cation channel PIEZO1 has been implicated in sensing intrarenal pressure and regulating urinary osmoregulation, but its role in kidney cystogenesis is unclear. Methods. We hypothesized that altered mechanotransduction contributes to cystogenesis in autosomal dominant polycystic kidney disease and that activation of mechanosensitive cation channels could be a therapeutic strategy. Results. We demonstrate that Yoda1, a PIEZO1 activator, increases intracellular calcium and reduces forskolin-induced cAMP levels in mouse inner medullary collecting duct (mIMCD3) cells. Notably, knockout of polycystin-2 attenuated the efficacy of Yoda1 in reducing cAMP levels in mIMCD3 cells. Yoda1 also reduced forskolin-induced mIMCD3 cyst surface area in vitro and cystic index in mouse metanephros ex vivo in a dose-dependent manner. However, collecting duct–specific PIEZO1 knockout neither induced cystogenesis in wild-type mice nor altered cystogenesis in the Pkd1RC/RC mouse model. Conclusions. These findings support the potential role of PIEZO1 agonists in mitigating cystogenesis by increasing intracellular calcium and reducing cAMP levels, but the unaltered in vivo cystic phenotype after PIEZO1 knockout in the collecting duct suggests possible redundancy in mechanotransductive pathways.